2021
DOI: 10.1021/acs.orglett.1c03451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Bicyclo[2.2.1]heptane Skeleton with Two Oxy-Functionalized Bridgehead Carbons via the Diels–Alder Reaction

Abstract: We describe a synthetic method for a bicyclo[2.2.1]­heptane skeleton with two oxy-functionalized bridgehead carbons. This method involves an intermolecular Diels–Alder reaction using 5,5-disubstituted 1,4-bis­(silyloxy)-1,3-cyclopentadienes, the diene structure of which has never been synthesized. Furthermore, the intramolecular Diels–Alder reaction using a diene bearing a dienophile moiety at the C-5 position can provide a tricyclic carbon framework that includes the bicyclo[2.2.1]­heptane skeleton. The novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Asymmetric synthesis of 17 was performed using a modified version of our reported synthetic method. 16 In brief, treatment of 2-methyl-1,3-cyclopentanedione (18) with acrolein diethyl acetal in water at 40 °C induced the in situ generation of acrolein, followed by the Michael addition of 18 to acrolein to afford aldehyde 19. Although the Kigoshi group has reported a similar reaction in the presence of acetic acid, 17 we demonstrated that this reaction does not require an acid catalyst because 18 acts as a Brønsted acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric synthesis of 17 was performed using a modified version of our reported synthetic method. 16 In brief, treatment of 2-methyl-1,3-cyclopentanedione (18) with acrolein diethyl acetal in water at 40 °C induced the in situ generation of acrolein, followed by the Michael addition of 18 to acrolein to afford aldehyde 19. Although the Kigoshi group has reported a similar reaction in the presence of acetic acid, 17 we demonstrated that this reaction does not require an acid catalyst because 18 acts as a Brønsted acid.…”
mentioning
confidence: 99%
“…First, we synthesized a precursor for the intramolecular aldol reaction (Scheme ). Asymmetric synthesis of 17 was performed using a modified version of our reported synthetic method . In brief, treatment of 2-methyl-1,3-cyclopentanedione ( 18 ) with acrolein diethyl acetal in water at 40 °C induced the in situ generation of acrolein, followed by the Michael addition of 18 to acrolein to afford aldehyde 19 .…”
mentioning
confidence: 99%
“…5 Our group recently reported that 1,4-bis(silyloxy)cyclopentadiene 3 derived from 1,3-cyclopentanedione 4 induces the intramolecular Diels-Alder reaction to afford the tricyclic compound 5 (Scheme 1b). 6 This reaction further shows the utility of 2,2-disubstituted 1,3-cyclopentanediones in synthetic organic chemistry.…”
mentioning
confidence: 99%